2009
DOI: 10.1128/mcb.00884-08
|View full text |Cite|
|
Sign up to set email alerts
|

Coactivation of Estrogen Receptor β by Gonadotropin-Induced Cofactor GIOT-4

Abstract: Estrogen exerts its diverse effects through two subtypes of estrogen receptors (ER), ER␣ and ER␤. Each subtype has its own distinct function and expression pattern in its target tissues. Little, however, is known about the transcriptional regulatory mechanism of ER␤ in the major ER␤-expressing tissues. Using biochemical methods, we identified and described a novel ER␤ coactivator. This protein, designated GIOT-4, was biochemically purified from 293F cells. It coactivated ER␤ in ovarian granulosa cells. GIOT-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Other coregulatory proteins have been shown to interact specifically with one receptor or the other. For instance, GIOT-4 and thyroid hormone receptor-associated protein 220 have been identified as ER␤-specific coactivators (48,49), whereas BRG1-and hBRM-Associated Factor 57 or calmodulin selectively regulates ER␣-mediated transcription (50,51). More recently, a comparative computational analysis of the nuclear interactomes of the 2 ER subtypes revealed only 70 common proteins (on a total of 498 partners), thus likely explaining the distinct biological roles of the 2 ERs (52).…”
Section: Discussionmentioning
confidence: 98%
“…Other coregulatory proteins have been shown to interact specifically with one receptor or the other. For instance, GIOT-4 and thyroid hormone receptor-associated protein 220 have been identified as ER␤-specific coactivators (48,49), whereas BRG1-and hBRM-Associated Factor 57 or calmodulin selectively regulates ER␣-mediated transcription (50,51). More recently, a comparative computational analysis of the nuclear interactomes of the 2 ER subtypes revealed only 70 common proteins (on a total of 498 partners), thus likely explaining the distinct biological roles of the 2 ERs (52).…”
Section: Discussionmentioning
confidence: 98%
“…127,373 Recent work in KGN cells suggest that GIOT-4, a cofactor regulated by FSH, may act to increase ERβ expression as well as work in combination with ERβ to regulate target genes in follicles. 423 Although this work was done primarily in KGN ovarian cells, it was also reported that GIOT-4 and ERβ are co-localized in growing follicles providing support for the co-regulation. The expression of GIOT-4 has not been examined in in vitro-cultured granulosa cells.…”
Section: Rodentsmentioning
confidence: 96%
“…One of the hypotheses to explain the inhibitory effect of ERβ on E2 regulation of gene expression and cell proliferation implies a differential recruitment of transcriptional coregulators by the two ER subtypes. Previous studies have reported ERβ [54,55] or ERα [56,57]…”
Section: Effect Of Rip140 On Erα and Erβmentioning
confidence: 95%